2014
DOI: 10.4236/as.2014.510093
|View full text |Cite
|
Sign up to set email alerts
|

Solar Radiation Interception, Dry Matter Production and Yield among Different Plant Densities of <i>Arachis spp</i>. in Ibadan, Nigeria

Abstract: The production of grain legumes is becoming a popular practice in the humid south western Nigeria. Apart from the decreasing trends observed in rainfall amount and duration as a result of climate change, solar radiation interception also constitutes a limitation to crop production because of persistent cloud cover. A trial was conducted at the University of Ibadan experimental site to determine the effect of different plant densities of Arachis spp. on solar radiation interception, dry matter production and yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…In contrast, variety K6 (V4) had the lower number of pods plant -1 at 19.8. These results align with the study by Oluwasemire et al [10], where different groundnut varieties exhibited varying pod production capacities. It's worth noting that these differences in varieties can be attributed to genetic traits and adaptability to specific environmental conditions.…”
Section: Number Of Pods Plant -1supporting
confidence: 92%
“…In contrast, variety K6 (V4) had the lower number of pods plant -1 at 19.8. These results align with the study by Oluwasemire et al [10], where different groundnut varieties exhibited varying pod production capacities. It's worth noting that these differences in varieties can be attributed to genetic traits and adaptability to specific environmental conditions.…”
Section: Number Of Pods Plant -1supporting
confidence: 92%
“…CIPAR increased with increasing planting density whereas, dry matter production decreased against planting density. However, Oluwasemire and Odugbenro (2014) in soya bean reported that higher solar radiation intercepted increased radiation use efficiency (RUE), and dry matter production under uniform planting density. That could be due to the high competition and shading effect in high planting density.…”
Section: Light Interception and Dry Matter Productionmentioning
confidence: 99%
“…371 groundnut germplasm from diverse origins were randomly selected from early, medium, and late maturity groups (Table 1S). These germplasm collections came from Australia (1), East Africa (19), Middle Africa (5), North Africa (3), West Africa (33), South Africa (34), Europe (8), North America (48), South America (29), South Asia (127), Southeast Asia (12), East Asia (14), Middle East Asia (3), West Asia (3), and unknown origin. The Gene bank, ICAR-Directorate of Groundnut Research, in Junagadh, Gujarat, India, provided groundnut genetic resources for this research.…”
Section: Experimental Materialsmentioning
confidence: 99%